Case report—Every thoracic surgeon's nightmare: cardiac and lung perforation during placement of Nuss bar for pectus excavatum - Beati, Federico; Frediani, Simone; Pardi, Valerio; Aloi, Ivan; Bertocchini, Arianna; Accinni, Antonella; Inserra, Alessandro (Frontiers in Pediatrics, 2023)
The prevalence of life-threatening complications (LTCs) related to the minimally invasive repair of pectus excavatum (MIRPE) are unknown and underreported. The aim of this study is to contribute to the real prevalence of these rare but dramatic complications and show what went wrong in order to prevent it in the future.A 15-year-old male, affected by Pectus Excavatum (PE) with severe asymmetric deformity of the chest wall was evaluated for elective corrective surgery. Preoperative computed tomography showed a Haller index of 5.7, and Correction Index of 0.40. MIRPE was performed under right-video-assisted thoracoscopy. After placement of bar-introducer cardiac arrhythmias occurred. The introducer was removed, and massive bleeding was noted.Emergency Clamshell thoracotomy was performed, and cardiac surgeon immediately alerted.A first pulmonary wound was found and controlled. Two cardiac lacerations were found: on the interventricular wall and on the right atrium. Under cardiopulmonary bypass cardiac lacerations were sutured and other three pulmonary wounds repaired. Urgent fasciotomy was performed for compartmental syndrome of the right lower art after femoral cannulation.Pulmonary distress occurred; patient was admitted on ECMO in intensive care unit. Right Lower Lobectomy was carried out on 5 th post-operative day due to massive pulmonary bleeding and temporary tracheostomy was necessary. The patient was discharged to rehabilitation after 3 months with no brain injuries, minor hearing loss, and tracheostomy.We want to maintain high alertness on this procedure. Reporting these scaring complications contributes to the real prevalence of LTCs. We suggest the use of bilateral thoracoscopy and crane elevator in severe sternal defects.We also suggest to have a cardiac surgeon available in the hospital because cardiac perforation.